Rancangan dan Implementasi Sistem Pendukung Keputusan Pemilihan Bibit Tanaman Karet - Ariska, Dewi M.; Astuti, Indah F.; Agus, Fahrul (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
Hevea brasiliensis, commonly known as rubber plants, is a plantation commodity that holds acrucial position in the economic activities of Indonesia. At one point in history, Indonesia held aprominent position in global rubber production, surpassing the output of other nations. The initialstage in establishing a successful rubber plantation involves the careful selection of outstanding plantseeds that possess the capacity to yield substantial quantities of latex characterized by exceptionalquality. CV. Eja Nursery, located in South Prangat Village, Marangkayu District, Kutai KartanegaraRegency, is recognized as one of the rubber plantations in the province of East Kalimantan. Theprocess of seed selection at this plantation for rubber trees is now conducted manually, lacking afoundation in scientifically informed decision-making. Conversely, advancements in the realm ofscience and technology about decision support systems (DSS) software have permeated manysectors, including the rubber plantation industry. The objective of this study is to design andimplement a DSS to select rubber plant seeds at CV. Eja Nursery. The system design employs thedata flow methodology, while the system itself is implemented on a web-based platform. The presentstudy has developed a web-based decision support system aimed at assisting the staff of CV. EjaNursery in the selection of high-quality rubber plant seeds.